APPROACH OF BIOGRAPHY OF OBJECTS: A PASSAGE FROM PROFANE TO SACRED - Jahra, Fierda Al; Marwoto, Irmawati (International Review of Humanities Studies, 2024)
This paper discusses the life journey of buildings through the Biography of Things approach taken through a case study of the Bouwploeg building which is currently the Cut Meutia Mosque. The change from an office building as a profane building to a mosque as a sacred building is the reason for the biography of things approach. This research uses the main data in the form of the Cut Meutia Mosque building, which is still standing in Menteng, Central Jakarta. The research method used in this research is based on the K. R. Dark framework which consists of data sources, data, evidence, and interpretation. The results of this research show that there are physical changes, functions, and meanings in the building's life journey to become the Cut Meutia Mosque as a sacred building. This can be seen from the changes in materials and landscape. As well as the role of agency and structure behind it so that there can be a change in the building from profane to sacred.